The Effectiveness of the Implementation of Mood Management on Sad Person Screening with Suicide Risk - Firmawati, Firmawati; Biahimo, Nur Uyuun I.; Mile, Niken (Newinera Publisher, 2024)
Mood changes are caused by a functioning thought process that experiences maladaptive behaviors that generate negative thoughts that cause the patient to descend behaviors such as withdrawal from the environment associated with depressive episodes, which results in maladaptive coping mechanisms that increase the risk of suicide, so that Mood management can be given to reduce the burden of the problem. The aim of the study was to analyze the effectiveness of the application of mood management to SAD PERSON screening with suicide risk. The research method used a pre-experimental research design with one group pre posttest design, the research subjects of patients at risk of suicide were 15 patients with a total sampling technique, the research instrument used a SAD PERSON observation sheet and the data was analyzed by the Wilcoxon non-parametric statistical test. The results showed that the average score of symptoms before the implementation of mood management was 6.73 with a standard deviation of 1.033 and the average score after the implementation of mood management was 4.80 with a standard deviation of 1.207, and the p-value was obtained with a value of 0.001 (<α 0.05). Conclusion of the effective application of mood management to SAD PERSON screening with suicide risk in the Limboto Health Center.